1995
DOI: 10.1111/j.1440-1746.1995.tb01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity and analysis of mutation of p53 in hepatocellular carcinoma

Abstract: Thirty-six hepatocellular carcinoma (HCC) tissues obtained from 34 patients were classified according to histological diagnosis into six well-differentiated HCC, 20 moderately differentiated HCC and 10 poorly differentiated HCC. High molecular weight DNA was prepared from each tumour and the corresponding non-tumour tissue. Loss of heterozygosity (LOH) on chromosomes 4q, 5q, 10q, 11p, 16q, 17p, mutation of the p53 gene and polymorphism of intron 25 of the retinoblastoma (RB) gene were simultaneously analysed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 20 publications
(1 reference statement)
4
44
0
Order By: Relevance
“…Although loss of p53 has been reported in HCC. [19][20][21] and other solid tumors, it was rare in the present series. Our results indicate that loss of p53 is not a primary factor in the development of HCV-HCC and that other genes on 17p are involved in hepatocellular carcinogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…Although loss of p53 has been reported in HCC. [19][20][21] and other solid tumors, it was rare in the present series. Our results indicate that loss of p53 is not a primary factor in the development of HCV-HCC and that other genes on 17p are involved in hepatocellular carcinogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…The association between allelic loss on chromosome 16q and the progression of human HCC has been proposed by several groups (Tsuda et al, 1990;Nishida et al, 1992;Yumoto et al, 1995). Tsuda et al (1990) reported that allelic loss between HP and CTRB loci occurred more frequently in HCCs of poor differentiation and large size, and with metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…Twenty-four (58.5%) HCCs were detected in cirrhotic livers. Nine cases (22%) were small (≤ 3 cm) and 32 (78%) were advanced (> 3 cm) HCCs (Yumoto et al, 1995). Tumour differentiation was graded according to the criteria of Kanai et al (1987): seven (17%) HCCs were well-differentiated, 23 (56%) were moderately differentiated and 11 (27%) were poorly differentiated according to this grading system.…”
Section: Tissue Selection and Dna Extractionmentioning
confidence: 99%
“…5,6 Many studies on HCCs have shown LOH on chromosomes 1p, 1q, 4q, 5q, 8p, 11p, 13q, 16q, and 17p. 7 In particular, the LOH and mutations of the RB gene on chromosome 13q and the P53 gene on 17p are frequently found. 7,8,9 However, such genetic changes have been reported to occur mainly in the late stage of hepatocarcinogenesis.…”
mentioning
confidence: 99%
“…7 In particular, the LOH and mutations of the RB gene on chromosome 13q and the P53 gene on 17p are frequently found. 7,8,9 However, such genetic changes have been reported to occur mainly in the late stage of hepatocarcinogenesis. If genetic changes of M6P/IGF2R gene occur in early hepatic neoplasms, they would be extremely important because they could serve as a useful marker for differential diagnosis of small hepatic lesions, especially with biopsy samples.…”
mentioning
confidence: 99%